Examining the Attitudes of Students in Secondary Education Towards Physical Education and Sports Class in Terms of Some Variables - Fuat Erduğan; Hakkı Toksöz; Cem Kurt (Türk Spor ve Egzersiz Dergisi)
The purpose of this study was to compare some variables like gender, class level, engaging in sports outside of the school, sports participation status of parents, having an indoor sports facility of students studying in Edirne province secondary schools by determining their attitudes towards Physical Education and Sports class. The sample of the study consisted of 1789 students from 7th grades (483 male, 480 female) and 8th grades (424 male and 402 female). To determine the attitudes of students towards physical education class ‘Physical Education Class Attitude Scale’ (PECAS) developed by Sherrin and Toulmin and adapted to Turkish by Özer and Aktop (2003) was used. Statistical analysis showed that there was a significant difference between gender, class level, engaging in sportive activities outside of the schools variables in terms of physical education attitude scale total score and there was no statistically significant difference between the scale scores of sports participation status of parents, and having an indoor sports facility variable. Attitude scale scores of male students were found to be higher than female students (p=0,05). Attitude scale scores of 7th grade students were found to be higher than 8th grade-students (p0,05). As a result, the results obtained from the current study indicate that the attitudes of secondary school students owards physical education class were affected by gender, class level and age. It can be concluded that these factors were recommended to be taken into consideration in planning physical education lessons by relevant institutions to increase the attitudes of students towards physical education class.